Anthracene-containing polymers toward high-end applications. (July 2018) - Van Damme, Jonas; Du Prez, Filip
Abstract: Anthracene, with its unique properties originating from the linearly fused benzene ring structure, has a long history in polymer science in numerous application areas. The most commonly used reasons are their (tunable) luminescence, easy energy and charge transfer as well as unique photo-and thermoreversible dimerization properties. Aside from [4 + 4]-photocycloadditions, anthracene is also able to undergo extremely fast Diels–Alder reactions with maleimides. The use of (non)reactive anthracene moieties in polymers is therefore following a constant publication increase that is expected to continue in the future in order to meet the need for more advanced materials. This review aims to give a critical overview of the literature dealing with anthracene-containing polymers and provide some insights for future research directions.